The sponge effect and carbon emission mitigation potentials of the global cement cycle - Cao, Zhi; Myers, Rupert J.; Lupton, Richard C.; Duan, Huabo; Sacchi, Romain; Zhou, Nan; Reed Miller, T.; Cullen, Jonathan M.; Ge, Quansheng; Liu, Gang (Nature communications, 2020)
Cement plays a dual role in the global carbon cycle like a sponge: its massive production contributes significantly to present-day global anthropogenic CO 2 emissions, yet its hydrated products gradually reabsorb substantial amounts of atmospheric CO 2 (carbonation) in the future. The role of this sponge effect along the cement cycle (including production, use, and demolition) in carbon emissions mitigation, however, remains hitherto unexplored. Here, we quantify the effects of demand- and supply-side mitigation measures considering this material-energy-emissions-uptake nexus, finding that climate goals would be imperiled if the growth of cement stocks continues. Future reabsorption of CO 2 will be significant (~30% of cumulative CO 2 emissions from 2015 to 2100), but climate goal compliant net CO 2 emissions reduction along the global cement cycle will require both radical technology advancements (e.g., carbon capture and storage) and widespread deployment of material efficiency measures, which go beyond those envisaged in current technology roadmaps. Cement plays a dual role in the carbon cycle like a sponge. Here, the authors employ a dynamic model to quantify such sponge effect and concluded that deep decarbonization of the global cement cycle will require radical technology advancements and widespread deployment of material efficiency measures.